2022
DOI: 10.1111/jgs.17880
|View full text |Cite
|
Sign up to set email alerts
|

A paradigm shift—Loneliness as a root cause of symptom distress among older adults

Abstract: This editorial comments on the article by https://onlinelibrary.wiley.com/doi/10.1111/jgs.17796. in this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…If depression is recognized among spouses, clinical teams can offer individualized pharmacologic and psychosocial interventions 8 . For loneliness, structured clinical frameworks also exist which can guide next steps and connect individuals to social interventions 6,24 . We hypothesize that addressing loneliness as an upstream approach might prevent depression, since a recent longitudinal study 4 identified loneliness as a powerful predictor of downstream depression, with the risk of depression from loneliness persisting for over a decade after loneliness was first reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If depression is recognized among spouses, clinical teams can offer individualized pharmacologic and psychosocial interventions 8 . For loneliness, structured clinical frameworks also exist which can guide next steps and connect individuals to social interventions 6,24 . We hypothesize that addressing loneliness as an upstream approach might prevent depression, since a recent longitudinal study 4 identified loneliness as a powerful predictor of downstream depression, with the risk of depression from loneliness persisting for over a decade after loneliness was first reported.…”
Section: Discussionmentioning
confidence: 99%
“…8 For loneliness, structured clinical frameworks also exist which can guide next steps and connect individuals to social interventions. 6,24 We hypothesize that addressing loneliness as an upstream approach might prevent depression, since a recent longitudinal study 4 identified loneliness as a powerful predictor of downstream depression, with the risk of depression from loneliness persisting for over a decade after loneliness was first reported. This mechanism can be evaluated in future longitudinal studies of spouses of PLwD and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with the extant literature that demonstrates higher levels of anxiety and depression, as single symptoms, are associated with higher levels of loneliness and social isolation as well as decreases in social support. 52 Being unemployed and having a lower annual household income were additional risk factors for being in the two worst profiles. Of note, 23.6% of the patients in these two classes reported an annual income of <$30,000.…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…Applying this conceptualisation to existing research on social connection at the end of life reveals that previous work has been rather fragmented. Using mainly a sociodemographic lens, previous work has focused on structure (eg, whether someone is married or lives alone) or function components (eg, social support or caregiver burden) of social connection 14 , 15 while paying less attention to quality components (eg, individuals' perceptions and evaluations of their relationships). Loneliness has been the predominant focus in studies of subjective experiences of social connection at the end of life.…”
Section: Introductionmentioning
confidence: 99%